The effect of fermented soybean (tempeh) supplementation among active pulmonary tuberculosis patients with standard therapy in Indonesia - Setiawan, Budhi; Justus Liebig University Giessen (My University, 2016)
Malnutrition due to wasting is a common feature in active pulmonary tuberculosis (TB) patients. Reduction in lean mass due to wasting can cause physical function impairment in people with active TB. Standard TB treatment alone improves nutritional status, but it might not be sufficient to achieve adequate nutritional recovery especially in food insecure areas. Tempeh is recognized as a nutritious and affordable food which is commonly consumed in many households in Indonesia. The first objective was meant to prepare tempeh as a suitable food supplement in the dietary intervention study. Its purpose was to analyze the effect of stir-frying on acceptability, chemical contents and antioxidant activities of tempeh. Second objective was, to determine the efficacy of tempeh supplementation on changes in body weight and physical ability in newly diagnosed active pulmonary TB patients with standard therapy. The intervention study using tempeh was carried out in the Lung hospital, Surabaya, Indonesia. Newly diagnosed active pulmonary TB patients participated in the study between November 2013 and February 2015. Sensory evaluation was conducted by administering a questionnaire along with tempeh samples. Fermentation of soybean was carried out in the solid state using raw soybeans (Glycine max) and was inoculated with a starter containing Rhizopus oligosporus. The total phenolic content of uncooked and stir-fried tempeh samples was examined using Folin-Ciocalteu s method and the phytic acid (PA) level was analyzed by high-performance liquid chromatography (HPLC). Antioxidant activities of tempeh samples were measured by the thiobarbituric acid reactive substance (TBARS) and ferric ion reducing/antioxidant power (FRAP) methods. Body weight of the patients was evaluated by measuring the change in body weight. Physical function change was assessed using handgrip strength and a six-minute walk test (6MWT). Static force from the dominant hand of patients was measured by squeezing a baseline dynamometer. Assessment of caloric and protein intakes was estimated by 24-hour dietary recall. The intervention group (n=65) received the standard treatment of TB and an additional 166.5 grams of cooked tempeh per day for two months while the control group (n=64) received only standard TB treatment. The outcome assessments were measured before and after the supplementation period for both groups. Sensory evaluation revealed that stir-fried tempeh was more acceptable than other traditional cooking methods among healthy volunteers. In comparison with uncooked tempeh samples, stir-frying increased content of fat and protein, but reduced carbohydrate, iron, zinc, and phytic acid levels of tempeh. Stir-fried tempeh samples presented lower total phenolic content and FRAP assay result. However, stir-fried tempeh samples showed a higher inhibition of TBARS formation. Tempeh supplementation for two months resulted in a higher body weight change among active pulmonary TB patients in the intervention group (2.80 ± 2.33 kg) compared with the control group (1.44 ± 2.42 kg, p = 0.02). Patients in the intervention group gained 1.36 kg more weight than those in the control group. Patients in the intervention group showed a higher handgrip strength change (3.90 ± 4.50 kg) than in the control group (0.84 ± 4.83 kg, p < 0.001). The gain in handgrip strength in the intervention group was 3.06 kg more than in the control group. In addition, handgrip strength value in the intervention group (28.94 ± 10.13 kg) was higher than in the control group (25.54 ± 9.04 kg, p = 0.046) at month 2. The change in 6MWT distance in the intervention group (49.67 ± 58.49 m) was greater than in the control group (25.75 ± 56.85 m, p = 0.02). The distance gain in 6 MWT was 23.92 m higher in the intervention group than in the control group. Protein and caloric intake resulted in no significant difference in both groups. In summary, tempeh is a nutritious food and contains bioactive components, but high cooking temperatures could change its chemicals properties and antioxidant activities. Daily consumption of boiled tempeh for two months among patients with active pulmonary TB on standard therapy showed a positive effect on weight gain and physical function change.
Keywords: ddc:610